Child’s Rights to Participate in Particular EU Legal Sources - Wopera, Zsuzsa (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:This chapter of the book will analyse the most important European Union legal sources in which the child’s right to participate appears. The chapter will primarily and intensively analyse EU legal sources concerned with family law cases with cross-border implications in the field of judicial cooperation in civil matters from the 1998 Brussels II Convention to the Brussels IIb Regulation, which entered into force on August 1st 2022. This chapter will also present the development of the regulation on the expression of the child’s views in these legal sources and the relevant jurisprudence of the Court of Justice of the European Union. In addition to the secondary sources of EU law, this part of the book also deals in detail with the relevant provisions of the Charter of Fundamental Rights of the European Union and the EU Strategy on the Rights of the Child, as well as the joint project of the Council of Europe and the European Commission on child-friendly justice, launched in January 2024.  Keywords: participation rights, judicial cooperation in civil matters, family law cases with cross-border implications, Charter of Fundamental Rights of the European Union, Brussels IIb Regulation, hearing of the child, child who is capable of forming views, genuine and effective opportunity to express views